Clinical and genetic characteristics of adult patients with familial Mediterranean fever at a German tertiary referral centre - Dorothea Reck; Jörg Christoph Henes; Sebastian Jonas Saur (BMC Rheumatology, 2026)
Abstract Objective To characterise the clinical and genetic profile of adult familial Mediterranean fever (FMF) patients at a German tertiary referral centre and examine genotype–phenotype associations. Methods In this prospective single-centre registry study (October 2019–March 2021), 95 adult FMF patients at University Hospital Tübingen were evaluated using structured questionnaires and medical record review. All patients had a pre-existing clinical diagnosis of FMF based on the Tel Hashomer and/or Eurofever/PRINTO criteria. Demographic data, clinical manifestations, treatment, and MEFV mutations were analysed. Patients were stratified by mutation status (homozygous M694V, heterozygous/compound-heterozygous M694V, other mutations). Statistical analyses included the Fisher–Freeman–Halton exact test and ANOVA. Variants were classified according to the INSAID consensus classification; R202Q was treated as a benign polymorphism. All subgroup comparisons were exploratory and were not corrected for multiple testing. Results Median age was 36 years, with median symptom onset at 10 years. Most patients were of Turkish origin (74.7%), and 59.6% reported a family history of FMF. Common manifestations included abdominal pain (90.5%), arthralgia/arthritis (75.8%), fever (66.3%), and chest pain (52.6%). Colchicine was used in 96.8% of patients, while 38.3% received biologic therapy, a figure influenced by concurrent participation in a tocilizumab trial at our centre. MEFV analysis had been performed in 91 of the 95 patients (95.8%); among these, at least one MEFV variant was detected in 87 (95.6%), with M694V being the most frequent variant (61.5%). Homozygous M694V patients showed earlier disease onset (nominal p = 0.02) and higher rates of arthralgia/arthritis (nominal p = 0.035). Amyloidosis occurred in one patient with homozygous M694V. Conclusion This cohort demonstrates typical FMF features with a predominance of the M694V mutation. Homozygosity for M694V is associated with earlier disease onset and increased musculoskeletal involvement. Subgroup findings are exploratory and require confirmation in independent cohorts.